Pengaruh Motivasi Kerja, Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan PT Telkomsel Bandar Lampung - Novita Iin Saputri; Defrizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Employee performance at PT. Telkomsel Bandar Lampung experienced a decline, indicated by a decrease in high performing employees and an increase in employees with poor performance. The decline in employee performance was in line with the decline in sales that did not meet the company's target. This research aims to analyze the effect of work motivation, work environment, and organizational culture on the employee performance of PT. Telkomsel Bandar Lampung. The population and sample used are 70 employees of PT. Telkomsel Bandar Lampung. Data were collected through a questionnaire and the technique used is multiple linear regression analysis. This study found that work motivation, work environment, and organizational culture have a significant influence on employee performance of PT. Telkomsel Bandar Lampung.